2022
DOI: 10.3390/ijms232214315
|View full text |Cite
|
Sign up to set email alerts
|

Dual Modification of Porous Ca-P/PLA Composites with APTES and Alendronate Improves Their Mechanical Strength and Cytobiocompatibility towards Human Osteoblasts

Abstract: Synthetic implants are used to treat large bone defects that are often unable to regenerate, for example those caused by osteoporosis. It is necessary that the materials used to manufacture them are biocompatible and resorbable. Polymer-ceramic composites, such as those based on poly(L-lactide) (PLLA) and calcium phosphate ceramics (Ca-P), are often used for these purposes. In this study, we attempted to investigate an innovative strategy for two-step (dual) modification of composites and their components to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…As mentioned earlier, these coupling agents are able to help the interaction between the polymer matrix and the ceramic matrix through two different functional groups, one of which can react with organic molecules, and the other can absorb inorganic surfaces in order to obtain a firm bond [ 240 ]. An example of a coupling agent often used is represented by Amino-propyl-triethoxy-silane (APTES) used as a surface modifier for glass and ceramic in order to increase the strength properties of biodegradable composites, as well as to improve the adhesion of the material to tissues [ 35 , 244 , 245 ]. Biernat et al [ 245 ] reported the functionalization of porous calcium phosphate ceramics (Ca-P)/ poly(L-lactide) (PLA) composites with APTES and alendronate in order to improve the mechanical properties and cytocompatibility.…”
Section: Biomedical Applications Of Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, these coupling agents are able to help the interaction between the polymer matrix and the ceramic matrix through two different functional groups, one of which can react with organic molecules, and the other can absorb inorganic surfaces in order to obtain a firm bond [ 240 ]. An example of a coupling agent often used is represented by Amino-propyl-triethoxy-silane (APTES) used as a surface modifier for glass and ceramic in order to increase the strength properties of biodegradable composites, as well as to improve the adhesion of the material to tissues [ 35 , 244 , 245 ]. Biernat et al [ 245 ] reported the functionalization of porous calcium phosphate ceramics (Ca-P)/ poly(L-lactide) (PLA) composites with APTES and alendronate in order to improve the mechanical properties and cytocompatibility.…”
Section: Biomedical Applications Of Membranesmentioning
confidence: 99%
“…An example of a coupling agent often used is represented by Amino-propyl-triethoxy-silane (APTES) used as a surface modifier for glass and ceramic in order to increase the strength properties of biodegradable composites, as well as to improve the adhesion of the material to tissues [ 35 , 244 , 245 ]. Biernat et al [ 245 ] reported the functionalization of porous calcium phosphate ceramics (Ca-P)/ poly(L-lactide) (PLA) composites with APTES and alendronate in order to improve the mechanical properties and cytocompatibility. After the functionalization with APTES, an increase in mechanical properties of the composites and an improvement in biocompatibility were observed through Sodium alendronate binds to hydroxyapatites in the bone.…”
Section: Biomedical Applications Of Membranesmentioning
confidence: 99%
“…Hydroxyapatite is the most documented calcium phosphate and can be used in a bulk form as a coating and/or cement [27,28]. This material can be classified according to its porosity, phase, and processing method.…”
Section: Reduction In Stress Shielding With Carbon Fiber Prosthesesmentioning
confidence: 99%
“…Under the same constraint and load conditions shown in Figure 4a, the results on the von Mises stress distribution for the rod topologically optimized in composite material are reported in Figure 11. Hydroxyapatite is the most documented calcium phosphate and can be used in a bulk form as a coating and/or cement [27,28]. This material can be classified according to its porosity, phase, and processing method.…”
Section: Reduction In Stress Shielding With Carbon Fiber Prosthesesmentioning
confidence: 99%
See 1 more Smart Citation